Nanoformulations of bioactive compounds derived from essential oils with antimicrobial activity - Valentina Nieto Marín; Danieli Fernanda Buccini; Viviane Gomes da Silva; Ian Alejandro Fernandez Soliz; Octávio Luiz Franco (Nano Trends)
Nanomaterial-based platforms for the formulation of bioactive compounds derived from essential oils (dEOs) have attracted considerable attention due to their potential to enhance the stability, controlled release, and antimicrobial efficacy of these natural compounds. This review analyzes the various nanomaterial platforms used for dEOs, including polymeric nanoparticles, liposomes, cyclodextrin and chitosan complexes, and inorganic nanosystems. The synthesis methods, physicochemical properties, and characterization techniques associated with these nanomaterial platforms are reviewed to elucidate their impact on the formulation and stability of dEOs. Furthermore, the antimicrobial activity of dEO formulations against a wide range of pathogenic microorganisms is described, highlighting the potential applications of these platforms in the treatment of infections and food preservation. The review also discusses the current challenges and prospects in the field, aiming to provide valuable insights for researchers and industry professionals involved in the development of nanomaterial-based dEO delivery systems.